Perancangan Ulang Guest House 6 Lantai Semarang (Indonesian Journal of Civil Engineering Study, 2025)
Alongside Indonesia's ever-accelerating development. A secure and cozy place to live is one of the infrastructure and supporting services. Planning for multi-story buildings housing apartments is not equivalent to planning for single-story structures. To enable the intended building to be constructed in compliance with technical principles that are both affordable and safe to use, building planning is required to ascertain the necessary dimensions and amount of reinforcement. Structures that require special planning are those that pose a significant risk because of various elements, including the building's purpose, the type of structure it uses, and its location—whether or not it is in an earthquake-prone area. This project was planned with the advancement of civil engineering and the passage of time in mind, taking into account architectural considerations.The project's functional stability, affordability and ease of execution, the structure's capacity to handle the building system, and the surrounding environmental factors as a new home or dwelling in the city of Semarang. If a structure is prone to being noticeably tipped, shifted, or flipped during the course of the intended building, structural planning is vital to ensure that the structure is considered stable. Structural planning must adhere to the government's regulations.
Keywords: Roof structure; Column; Floor plate; Beam